2016-2020القدرة التفسيرية لمؤشر القيمة الإقتصادية المضافة في تغيرات القيمة السوقية لمؤسسات الإقتصادية المسعرة في البورصة – دراسة حالة - للفترة ) - عبد الرحيم بن تومي; عادل عزابي (My University, 2022)
This study aims to measure the explanatory capacity of the economic value-added indicator on the changes in the market value of companies quoted on the Algerian stock exchange, namely, Saidal Group, Biopharm Complex, Rouiba Foundation, El Aurassi Hotel and Alliance Insurance Company, during the period (2016-2020), where it was relied on building Linear regression models between the independent variable (Economic Value Added Index) and the market value of institutional stocks as a dependent variable based on panel data models using Eviews9 programs. The study concluded that there is a statistically significant correlation between the economic value of the institutions and their market value, as 45.6% of the changes in the market value can be explained based on the added economic value, while 54.4% are attributed to other factors. The study also found that the effect of EVA on the MV market value differs from one institution to another, due to the intrinsic characteristics of each institution, and the different sectors active in it, which calls for research and study of those factors that explain the remaining percentage of changes in the market value of the institution. ...................................................... تهدف هذه الدراسة إلى قياس القدرة التفسيرية لمؤشر القيمة الاقتصادية المضافة على تغيرات القيمة السوقية لمؤسسات مسّعرة في البورصة الجزائرية وهي مجمع صیدال، مجمع بیوفارم، مؤسسة رويبة، فندق الأوراسي و ر شكة ألیانس للتأمینات، وذلك 2020 (، حیث تّم الاعتماد على بناء نماذج إنحدار خطية بين المتغير المستقل )مؤشر القیمة الإقتصادية - خلال الفترة ) 2016 .Eviews المضافة( والقیمة السوقیة للأسهم المؤسسات كمتغير تابع بالاعتماد على نماذج بيانات البانل بإستخدام برنامج 9 وقد توصّ لت الدراسة إلى وجود علاقة إرتباطية ذات دلالة إحصائية بين القیمة الإقتصادية للمؤسسات والقیمة السوقیة لها، أذ أنّ 45,6 % من التغيرات الحاصلة في القيمة السوقية يمكن تفسيرها بناء على القيمة الاقتصادية المضافة، بینما على القیمة EVA %54,4 فتعود إلى عوامل أخرى. كما توصّلت الدراسة أيضا إلى اختلاف تأثير القیمة الاقتصادية المضافة من مؤسسة إلى أخرى، ويعود ذلك إلى الخصائص الجوهرية لكل مؤسسة، واختلاف القطاعات الناشطة بها، وهو MV السوقیة ما يستدعي البحث في تلك العوامل التي تفسّر النسبة المتبقیة لتغيرات القیمة السوقیة للمؤسسة ودراستها.